Šolski vrtovi v pomurski regiji - Ambrožič-Dolinšek, Jana (Revija za elementarno izobraževanje, 2021)
School-based learning has a long tradition in Slovenia and is now a globally recognized movement. We present the operation of school gardens in the most agricultural region of Slovenia, the Pomurje region, and their inclusion in the pedagogical process of science subjects. Half (19 out of 38) of the primary schools in Pomurje have school gardens. The decision to establish a school garden depends on the good will of the school management and the voluntary interest of the teachers. It would be necessary to include school gardening in science curricula. Garden-related activities contribute to the development of Pomurje as an important agricultural region.
Keywords: elementary school; gardening; learning; osnovna šola; Pomurje region; Pomurska regija; school garden; šolski vrt; učenje; vrtnarjenje